2016
DOI: 10.1124/jpet.115.229641
|View full text |Cite
|
Sign up to set email alerts
|

Roflumilast Increases Bacterial Load and Dissemination in a Model of Pseudomononas Aeruginosa Airway Infection

Abstract: Exacerbations present a major clinical problem in many patients suffering from chronic obstructive pulmonary disease (COPD). Roflumilast, an inhibitor of phosphodiesterase 4, has shown beneficial effects in several clinical trials and is currently widely used to prevent exacerbations in severe COPD. Roflumilast has anti-inflammatory properties that may interfere with potentially important host defense functions, including cytotoxic properties of neutrophils at sites of inflammation. Since chronic bacterial inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
5
9
0
Order By: Relevance
“…Notably, 100 mg/kg ROF induced increases in the number of neutrophils and KC levels in the plasma and the lung tissues of the mouse model [ 18 ]. Furthermore, Kasetty et al [ 19 ] demonstrated that ROF increases the plasma levels of IL6, MCP1, and TNF while suppressing the infiltration of neutrophils in the BALF after bacterial infection, similar to our observations. Therefore, we are conducting further studies to investigate the appropriate dosage and molecular mechanisms involved in that ROF treatment in the elastolytic enzyme and CSE-induced COPD model.…”
Section: Resultssupporting
confidence: 92%
“…Notably, 100 mg/kg ROF induced increases in the number of neutrophils and KC levels in the plasma and the lung tissues of the mouse model [ 18 ]. Furthermore, Kasetty et al [ 19 ] demonstrated that ROF increases the plasma levels of IL6, MCP1, and TNF while suppressing the infiltration of neutrophils in the BALF after bacterial infection, similar to our observations. Therefore, we are conducting further studies to investigate the appropriate dosage and molecular mechanisms involved in that ROF treatment in the elastolytic enzyme and CSE-induced COPD model.…”
Section: Resultssupporting
confidence: 92%
“…To our knowledge, the data we report are the first to ever report specifically on hospitalizationrequiring pneumonia in roflumilast users. This is of special interest since animal studies have shown that the immune-suppressive effect of roflumilast may have detrimental effects on the host response towards bacterial infections [19], and in being consistent with these, our data show a concerning high risk of pneumonia-hospitalizations in these severely ill, vulnerable COPD patients.…”
Section: Comparison With Other Studiessupporting
confidence: 87%
“…Randomized trials [4,[10][11][12][13][14][15] have demonstrated an improvement in FEV1 (pre-and post-bronchodilatory) as well as a decrease in moderate-severe COPD exacerbations [7,9,10,18]. Of special concern, animal experiments have shown deleterious effects of roflumilast in bacterial lung infectious with increased mortality and bacterial loads [19], and likewise concerning, roflumilast has been documented to reduce the release of chemokine cysteine-cysteine ligand (CCL)2, CCL3, CCL4, chemokine cysteine-X-cystein ligand (CXCL) 10 and TNF-α, which may severely compromise the host defense towards bacterial infections [20,21]. However, specific results regarding the risk of roflumilast on hospitalization-requiring pneumonias have not been reported in trial data, and data on severe (hospitalization-requiring) COPD exacerbations have been sparse and diverging [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that PDE4 serves an important role in inflammation (37) and that the PDE4 inhibitor ROF ameliorates airway inflammation induced by CS and LPS (2,3). The appropriated concentration of ROF was determined with reference to the previous studies (38-42). The present study confirmed that PWRE exerts an anti-inflammatory effect by suppressing the influx of inflammatory cells and the production of inflammatory molecules (Figs.…”
Section: Resultsmentioning
confidence: 99%